A comparative study of effect of dexmedetomidine in dose of 0.7µg/kg and clonidine in doses of 2µg/kg as premedication before general anaesthesia - Singh, Shipra; Nazir, Nazia (International Journal of Research in Medical Sciences, 2017)
Background: Alpha -2 adrenoceptor agonists have widely been used in anaesthesia and critical care as analgesics and sedatives. Both clonidine and dexmedetomidine, a more selective and specific α-2 agonist have been shown to decrease induction doses of i.v. anaesthetics and intraoperative opioid and volatile anaesthetic requirements for maintenance of anaesthesia resulting in more rapid recovery from anaesthesia and also a reduced need for pain medication in post-operative period, thereby reducing the length of stay. The current prospective randomised double blind study was undertaken to compare the effects of dexmedetomidine and clonidine, as i.v. premedication, on perioperative hemodynamics , reduction in dose of inducing agent and post-operative analgesia duration. Methods: A total of 60 ASA class I and II patients undergoing elective surgeries under general anesthesia were randomised into two groups. Group D- dexmedetomidine 0.7µg/kg, and group C- clonidine 2µg/kg. Drugs were given 15 minutes before induction. The cases were conducted under General anesthesia with endotracheal intubation using Propofol, Vecuronium, N2O and O2. Heart rate, blood pressure, dose of inducing agent and time of rescue analgesia were recorded. Results: The rise in mean arterial pressure and heart rate during intubation and extubation was lesser with group D as compared to group C. (p<0.05). Lesser amounts of inducing agent was required with group D as compared to group C (p<0.0001). Post-operative analgesia duration was more with group D as compared to group C (p<0.001). Conclusions: Study concluded that Dexmedetomidine had better control over hemodynamics as compared to clonidine when given as premedication, the drug dose used for induction was lesser and also the post-operative analgesia duration was longer with dexmedetomidine.